2017
DOI: 10.3390/ijms18081703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Highly Polluted Environment on Sperm Telomere Length: A Pilot Study

Abstract: High environmental pressure may impair male fertility by affecting sperm quality, but the real effect remains controversial. Herein, we assessed the influence of environmental exposure on telomere length (TL) in both leukocytes (LTL) and sperm cells (STL). A pilot biomonitoring study was conducted in 112 clinically healthy, normospermic men living in various areas of Campania region (South of Italy) with high (n = 57, High Group) or low (n = 55, Low Group) environmental pressure. TL analysis was assessed by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
3
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
4
22
3
1
Order By: Relevance
“…Another one study showed that young male residents in areas with high environment exposure had a significantly increased telomere length in sperm. These findings support the view that semen is a sensitive sentinel biomarker of environmental exposure [8].…”
Section: Environmental Factors Influencing Male Infertility (Exogenousupporting
confidence: 86%
“…Another one study showed that young male residents in areas with high environment exposure had a significantly increased telomere length in sperm. These findings support the view that semen is a sensitive sentinel biomarker of environmental exposure [8].…”
Section: Environmental Factors Influencing Male Infertility (Exogenousupporting
confidence: 86%
“…In total, 15 of the positively associated studies detected a sperm TL (STL) association (68-70,72,74-84), while 3 studies detected an LTL association (73,85,86), and one study detected both STL and LTL (71). In several studies, shorter STL was reported in association to infertility (72,76,78,80) while Vecoli et al reported an increase in STL in areas of high environmental exposure (77). Although Turner and Hartshorne found an association between female fertility and STL, they did not find a significant association for male fertility (39).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 99%
“…In patients with high BMI (>28 kg/m 2 ) compared with normal BMI, increased reactive oxygen species (ROS) activity in semen and sperm DNA fragmentation were found,these are factors linked to poorer sperm quality that may account for poorer IVF treatment outcomes 48,49. STL attrition is linked to ROS exposure in relation to environmental and lifestyle factors such as alcohol consumption and smoking [50][51][52]. However, Mishra and colleagues demonstrated that a mild increase in oxidative stress is beneficial for STL maintenance 53.…”
mentioning
confidence: 99%